Symptom Profiles of Children and Young People 12 Months after SARS-CoV-2 Testing: A National Matched Cohort Study (The CLoCk Study) - Snehal M. Pinto Pereira; Manjula D. Nugawela; Kelsey McOwat; Emma Dalrymple; Laila Xu; Shamez N. Ladhani; Ruth Simmons; Trudie Chalder; Olivia Swann; Tamsin Ford; Isobel Heyman; Terry Segal; et al. (MDPI AG, 2023)
Background: Although 99% of children and young people have been exposed to SARS-CoV-2, the long-term prevalence of post-COVID-19 symptoms in young people is unclear. The aim of this study is to describe symptom profiles 12 months after SARS-CoV-2 testing. Method: A matched cohort study of a national sample of 20,202 children and young people who took a SARS-CoV-2 PCR test between September 2020 and March 2021. Results: 12 months post-index-test, there was a difference in the number of symptoms reported by initial negatives who never tested positive (NN) compared to the other three groups who had at least one positive test (p < 0.001). Similarly, 10.2% of the NN group described five-plus symptoms at 12 months compared to 15.9-24.0% in the other three groups who had at least one positive test. The most common symptoms were tiredness, sleeping difficulties, shortness of breath, and headaches for all four groups. For all these symptoms, the initial test positives with subsequent reports of re-infection had higher prevalences than other positive groups (p < 0.001). Symptom profiles, mental health, well-being, fatigue, and quality of life did not vary by vaccination status. Conclusions: Following the pandemic, many young people, particularly those that have had multiple SARS-CoV-2 positive tests, experience a range of symptoms that warrant consideration and potential investigation and intervention.